Green lean six sigma journey: Conceptualization and realization. (2022) - Mohan, Jag; Rathi, Rajeev; Kaswan, Mahender Singh; Nain, Somvir Singh
Abstract: Increased globalized pressure, government policies on climate change quality characteristics have forced organizations to rethink their business operations. Generally, efficiency, customer satisfaction, responsibility, and profitability have been the key role for the organization. The readjustment customers approach and environment adjustment have imposed organization to device the actions that go on sustainable and the same time engage the expectations of customers. Green Lean Six Sigma (GLSS) is one of the inclusive approaches that reduce negative environmental impact, reduce waste from industries, and consistent improvability in industries. The most important benefits of GLSS are decreasing process variations, reduce defective products in the industry for eliminating waste that reduces energy consumption, and most probably reduces all negative environmental impacts. Environmental consideration is taken to eliminate waste and increase industry performance without the effect of negative environmental impacts. The purpose of this paper is to present an analysis of research on GLSS focusing on a systematic literature review and accelerate the organization to have ready for the application of sustainable GLSS practice by way of detailed understanding of realization.